(untitled) (Itinera, 2023)
A neo-cosmological sensibility seems to pervade many of today’s philosophical debates. But what does it mean to conceive of a cosmic totality after Kant and after the entrance of cosmology into the circle of sciences? What does this new sensibility entail and what are its consequences on our thought, sensibility, representations, and artistic practices? This issue aims to address these and other questions from different viewpoints and traditions, with particular attention to the aesthetic implications of the new philosophical cosmologies.